Prevalence, incidence and risk factors for Helicobacter pylori infection in a cohort of Portuguese adolescents (EpiTeen) - Bastos, J (2013)
Background: Helicobacter pylori infection is acquired mainly during childhood, but it may occur throughout life. Understanding the determinants of infection at different ages is essential to clarify dynamics of H. pylori related diseases and to design preventive strategies. Aim: To estimate the prevalence of H. pylori infection at the age of 13 and the incidence after a 3-year follow-up and to identify risk factors for infection. Subjects and methods: Adolescents born in 1990 were recruited in schools from Porto. Whole-cell anti-H. pylori IgG antibodies were quantified by ELISA. Prevalence ratios (PR) and incidence rate ratios (RR) adjusted for parental education were computed at baseline (n = 1312) and at follow-up (n = 280). Results: The prevalence was 66.2%, lower in subjects with more educated parents (PR = 0.72, 95%CI: 0.63–0.82), and higher for those having more than one sibling (PR = 1.10, 95%CI: 1.02–1.19) and for smokers (PR = 1.11, 95%CI: 1.02–1.20). The incidence was 4.1/100 person-years. Smoking (RR = 2.35, 95%CI: 1.16–4.75) and type of school (RR = 0.38, 95%CI: 0.16–0.95) were associated with the incidence of infection. Conclusions: Prevalence and incidence of H. pylori infection were high, suggesting that gastric cancer will remain an important public health problem in this generation of Portuguese. We identified smoking as a modifiable risk factor for infection.